Mathematical Modeling to Study Multistage Stem Cell Transplantation in HIV-1 Patients - Manar A. Al Qudah; Sana’a A. Zarea; Saoussan A. Kallel-Jallouli (Discrete Dynamics in Nature and Society)
Stem cells as a therapeutic measure for the treatment of different diseases have a great potential to give rise to different mature cells as they could be used to treat HIV-1 patients when provided with the convenient factors. Thus, this paper proposes a new mathematical model, represented by a system of ODEs, to study the effect of stem cell transplantation for HIV-1 patients. Since stem cells lineage passes through many stages to become more specialized cell types, investigating (theorizing) the best stage for these cells to be engrafted was needed. The proposed system of ODEs can help medicine make the right decision about the proposed therapy.